LA COMEDIA SEXUAL ESPAÑOLA DE PRINCIPIOS DE LOS SETENTA Y EL FILM REACCIONARIO (Res Publica. Revista de Historia de las Ideas Políticas, 2009)
…)Through an analysis of one of the better-known Spanish sexual comedies from the early seventies, No desearás al vecino del quinto, the author defends its extraordinary character, denying its status as yet another reactionary landista film, whose protagonist and center of reference were always the repressed macho hispánico. Both from a formal and a diegetic point of view (namely, given the self-reflexivity of the film, and its non-hostile look towards homosexuality), this film reveals its exceptional character (…)